2004
DOI: 10.1111/j.1582-4934.2004.tb00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estrogen and progesterone treatment on rat hippocampal NMDA receptors: Relationship to Morris water maze performance

Abstract: Ovarian hormones have several effects on the nervous system that extend beyond regulation of the reproductive functions. Estrogen is believed to have a neuroprotective effect, both in human [1] and animal models [2]. Estrogen protects the neurons from injury of different insults like β-amyloid and glutamate toxicity [3], oxidative stress [4] and ischemia [5]. Moreover, it enhances neuronal repair after injury [6] and neurite plasticity by regulating the number of synaptic inputs in pyramidal cells of the CA1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 52 publications
10
51
0
Order By: Relevance
“…The decline of hippocampal NPY attributable to the lack of ␤-estradiol may be involved in learning and memory disturbances and changes in mood, including increased anxiety states in women after menopause (medical or natural) (Hattiangady et al, 2005;Osterlund et al, 2005). These clinical observations are supported by animal studies, which also show that ovariectomy leads to decline in learning and memory and to increased anxiety in females, all of which can be corrected by ␤-estradiol replacement (El-Bakri et al, 2004;Imwalle et al, 2005). Similarly, changes in the NPY system are associated with disturbances in learning and memory as well as anxiety behaviors (Heilig, 2004;Redrobe et al, 2004).…”
Section: Discussionsupporting
confidence: 67%
“…The decline of hippocampal NPY attributable to the lack of ␤-estradiol may be involved in learning and memory disturbances and changes in mood, including increased anxiety states in women after menopause (medical or natural) (Hattiangady et al, 2005;Osterlund et al, 2005). These clinical observations are supported by animal studies, which also show that ovariectomy leads to decline in learning and memory and to increased anxiety in females, all of which can be corrected by ␤-estradiol replacement (El-Bakri et al, 2004;Imwalle et al, 2005). Similarly, changes in the NPY system are associated with disturbances in learning and memory as well as anxiety behaviors (Heilig, 2004;Redrobe et al, 2004).…”
Section: Discussionsupporting
confidence: 67%
“…While the 5E group displayed slower swim speeds during day 2 of testing compared to 10E, differences in motivation and motor ability are unlikely because distance covered was consistent with latency to escape. This nonlinear effect for the 5E rats to outperform the 10E and vehicle groups on spatial acquisition is consistent with other reports using a different treatment regimen with estradiol benzoate (Xu and Zhang, 2006) or low-dose tonic or cyclic estradiol treatment in young (El-Bakri et al, 2004) and middle-aged OVX female rats (Bimonte-Nelson et al, 2006;Fernandez and Frick, 2004). At the end of the training session in our study, we gave a probe trial to assess navigation strategies, which showed that all treatment groups learned the platform location.…”
Section: Effects Of Intermittent Estradiol Treatment On Hippocampal Fsupporting
confidence: 75%
“…Moreover, ElBakri et al (2004) indicated that low-dose estrogen usage showed better learning and memory than high-dose estradiol administration. Treatment with high doses of female sex hormones can decrease the dendritic spine and synapse in CA1 hippocampus (25). The current study indicated that doses of 1.5 and 2 μg of progesterone were effectively able to increase memory in a passive avoidance task.…”
supporting
confidence: 47%